(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This study analyzes the costs associated with providing elementary education to children with special needs (CWSN) under the SamagraShikshaAbhiyan in Lucknow District. Using data from various sources, including enrollment figures, financial allocations, and policy documents, the study highlights trends in CWSN enrollment, examines financial provisions, and identifies gaps in funding. The analysis reveals a generally positive trend in increasing enrollment in CWSN, with notable fluctuations in higher grades. Financial support, as outlined in the scheme, includes provisions for aids, teaching materials, and special educators. However, funding allocations show variability, indicating the need for more consistent financial support. The study concludes that while there have been significant investments in inclusive education, there is a need for stable and targeted funding to ensure effective and equitable support for CWSN. The findings offer actionable insights for policymakers to enhance the implementation of inclusive education programs and optimize resource allocation in the Lucknow District.